The Position of Distractors in Multiple-Choice Test Items: The Strongest Precede the Weakest - Lions, Séverin; Monsalve, Carlos; Dartnell, Pablo; Godoy, María Inés; Córdova, Nora; Jiménez, Daniela; Blanco, María Paz; Ortega, Gabriel; Lemarié, Julie (Frontiers in Education, 2021)
Middle bias has been reported for responses to multiple-choice test items used in educational assessment. It has been claimed that this response bias probably occurs because test developers tend to place correct responses among middle options, tests thus presenting a middle-biased distribution of answer keys. However, this response bias could be driven by strong distractors being more frequently located among middle options. In this study, the frequency of responses to a Chilean national examination used to rank students wanting to access higher education was used to categorize distractors based on attractiveness level. The distribution of different distractor types (best distractor, non-functioning distractors…) was analyzed across 110 tests of 80 five-option items administered to assess several disciplines in five consecutive years. Results showed that the strongest distractors were more frequently found among middle options, most commonly at option C. In contrast, the weakest distractors were more frequently found at the last option (E). This pattern did not substantially vary across disciplines or years. Supplementary analyses revealed that a similar position bias for distractors could be observed in tests administered in countries other than Chile. Thus, the location of different types of distractors might provide an alternative explanation for the middle bias reported in the literature for tests’ responses. Implications for test developers, test takers, and researchers in the field are discussed.